R&D Marketing Integration in New Product Development: The Case of the Telecommunications Industry in Malaysia (Preliminary Findings) (Malaysian Management Journal, 1997)
Developing new products in a complex environment, such as in the telecommunications industry, involves significant integrated effort-particularly between that of R&D and Marketing. The failure to integrate R&D and Marketing in new product development can result in over-designed, over-priced, and either obsolete or radically-advanced products with little customer value. This paper attempts to offer insights into R&D and Marketing integration in. the telecommunications industry in Malaysia. In general, only a few telecommunication companies have achieved effective R&D-Marketing integration which is significant in certain areas requiring the integration.